Reutilization of berry press residues in minced Baltic herring (Clupea harengus membras) – Effect on lipid oxidation and sensory characteristics during cold storage - Kakko Tanja; Damerau Annelie; Mejia Rios C.; Laaksonen Oskar; Yang Baoru (Academic Press, 2025)
Lipid oxidation is one of the main causes of quality deterioration in dark-muscled fish. This study investigated the effect of berry side streams of juice pressing or oil extraction at different concentrations on lipid oxidation and sensory quality of minced Baltic herring (Clupea harengus membras) stored at 1 ◦C. Lipid oxidation was assessed by determining the peroxide value and volatile secondary oxidation products. Generic descriptive analysis and gas chromatography-olfactometry were used to investigate the odor, flavor, and odor-active compounds of minces. Based on the peroxide value and formation of hexanal, 1-penten-3-ol, and 3,5-octadien-2-one, a concentration of 1.5 g/100 g of lingonberry-bilberry juice press residue and sea buckthorn juice press and oil extraction residue was sufficient to retard and reduce the extent of oxidation. Furthermore, the addition of these residues inhibited the formation of fishy odors during 3 days of storage. The control mince stored for 3 days showed the highest number and intensities of oxidation products such as (Z)-4-heptenal, 2,3-pentanedione, and (E,Z)-2,6-nonadienal, while their formation was retarded in the mince containing press residue from sea buckthorn. Berry press residues were efficient in controlling lipid oxidation of minced Baltic herring during storage and have the potential to mask potentially unpleasant fishy odor and flavor.